Post-TB lung function, quality of life, and radiographic findings in children - G.L. Becker; H. Kisembo; Y. Sato; L.H. Wendt; H. Aanyu-Tukamuhebwa; R. Nantanda; JB. Jackson; R.J. Blount; E. Wobudeya (IJTLD Open, 2025)
BACKGROUND: The long-term effects of pulmonary TB (PTB) on pediatric lung health are poorly understood. Our objective was to assess predictors of lung function and describe health-related quality of life (QoL) and chest radiograph findings in children following PTB treatment in Kampala, Uganda. METHODS: We performed a cross-sectional study of children aged 6–16 years who completed PTB treatment within the last five years compared to household controls with no history of active TB. Children underwent chest radiograph, St. George’s Respiratory Questionnaire, and spirometry. Mixed-effects regression models were performed to assess predictors of lung function impairment. RESULTS: We enrolled 73 children with prior TB and 49 controls. In univariate mixed-effects regression models, prior TB was associated with lower FEV1 and FVC Z-scores (p<0.05). In multivariate models, BMI-for-age Z-score predicted FVC-Z-score (p<0.001). Fibrosis and pleural thickening were common radiographic abnormalities among children with prior TB. Median SGRQ total score was higher among children with prior TB (p<0.001). CONCLUSION: Children with prior TB showed reduced lung function and QoL compared to household controls. Our findings support the need for routine clinical follow-up after TB treatment.